Tax Audits, Penalties, Enforcements, and Tax Compliance Among Small Retail Firms - Augustina Kwakye; Adjei Amaniampong; Bernard Opoku Frimpong; Benjamin Blavo (Yayasan Ilomata, 2025)
A major problem in developing countries, including Ghana, is the high rate of tax evasion. This has adverse implications for development as the government largely relies on tax revenue for embarking upon national developmental activities. There is therefore a need to explore avenues to prevent tax evasion and increase tax revenue by adopting measures that promote tax compliance. This study examined the effect of tax audits, firm knowledge, and tax penalty enforcement on tax compliance among firms in the Kumasi Metropolis in Ghana. The quantitative research approach was adopted. A sample of 50 firms was randomly selected. A logit multivariate regression technique was employed to analyze data. In relation to firm size, the study finds that tax audit, the firm’s knowledge and awareness of tax penalties, and the enforcement of tax penalties are positively related to tax compliance. The study therefore recommends that tax authorities increase tax auditing activities, disseminate more information on tax penalties, and enforce these penalties effectively. Through education, auditing, and enforcement of tax penalties, tax evasion could be reduced.